(untitled) (Research, Society and Development, 2022)
Cardiopulmonary arrest (CPA) is an event that causes the sudden interruption of cardiovascular activity, as well as the respiratory process, in which this stage presents the absence of respiratory movements, consciousness and heart rate. The study aims to analyze through the literature the strategies used to prevent cardiorespiratory arrest in the hospital environment. The study was carried out through an integrative review (IR). In this sense, two thematic categories were established in the study approach. The category entitled “strategies for the prevention of cardiorespiratory arrest in the hospital environment” presents preventive measures to avoid this clinical condition and reduce mortality, since CRA is most of the time irreversible, and the proposals for interventions are fundamental for the resoluteness. assistance, as well as for the promotion of health problems. The second category entitled “importance of the multidisciplinary team for the quality of care during cardiorespiratory arrest”, shows the resoluteness of teamwork for holistic care. Thus, the study contributed to new scientific evidence on the magnitude of this topic, despite the comprehensiveness in the literature, few studies answered the research objective.